Common Eider (Somateria Mollissima) Body Condition and Parasitic Load during a Mortality Event in the Baltic Proper. (August 2018) - Garbus, Svend-Erik; Lyngs, Peter; Christensen, Jens Peter; Buchmann, Kurt; Eulaers, Igor; Mosbech, Anders; Dietz, Rune; Gilchrist, H. Grant; Sonne, Christian
During late spring of 2007 and 2015, we observed unusually high mortality of Common Eiders (Somateria mollissima) on Christiansø in the Baltic Proper. The number of dead birds (2007: 125; 2015: 110) composed 5–10% of the total colony. In 2015, we collected 15 (12 adult females, three subadult males) of the 110 recently deceased Common Eiders for detailed autopsy. The average body mass of the females was 1, 040 g (920–1, 160 g) which is ca 60% lower than what can be expected of healthy females during wintertime. Similarly, for the subadult males the average body mass of 1, 203 g (1, 070–1, 300 g) comprised only 45% of what can be expected for healthy subadult males during winter. All 15 birds were thus severely emaciated and cachexic with general atrophy of muscles and internal organs. Hunger oedema, distended gall bladder, empty stomach, empty and dilated intestines and dilated cardiomyopathy were observed as well. In addition, all 15 Common Eiders were infected with high loads of the acanthocephalan parasite Polymorphus minutus. No gross morphological changes suggested toxicological, bacteriological or viral causes to the mortality. Taken together, our autopsy suggested starvation leading to secondary metabolic catabolism and eventually congestive heart failure. Five birds that were examined in 2007 showed the same symptoms. We suspect that the introduction of suboptimal feeding conditions in combination with a high parasite load over the last decade synergistically caused high physiological stress leading to population level effects manifested as high mortality.